A remark on John – Nirenberg theorem for martingales - Li, L. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
This paper is mainly devoted to establishing an extension of the John – Nirenberg theorem for martingales, more precisely, let 1 < p < ∞ and 0 < q < ∞. If the stochastic basis (F_n)_n≥ 0 is regular, then BMO_p,q = BMO_1 with the equivalent norms. Our method is to use a new atomic decomposition construction of the martingale Hardy space.